What everyone needs to know about Islam - Esposito, John L. (What everyone needs to know., 2002)
In the aftermath of the terrorist attacks of September 11th, there has been an overwhelming demand for information about Islam. As a leading expert, John Esposito has found himself called upon to speak to a wide range of audiences, including members of Congress, the Bush administration, government agencies, the military, and the media. Out of this experience, he has identified the most pressing questions people consistently ask about Islam. In What Everyone Needs to Know about Islam, Esposito presents in question-and-answer format the information that most people want to know. Esposito provides succinct, accessible, sensitive, and even-handed answers to questions that range from the general-"What do Muslims believe?" and "Who was Muhammad?"--To more specific issues like Is Islam compatible with modernization, capitalism and democracy? How do Muslims view Judaism and Christianity? Are women second-class citizens in Islam? What is jihad? Does the Quran condone terrorism? What does Islam say about homosexuality, birth control, abortion, and slavery?; As the editor of The Oxford Encyclopedia of Modern Islam and The Oxford History of Islam, and author of Unholy War and many other acclaimed works, John Esposito is one of America's leading authorities on Islam. This brief and readable book is the first place to look for information on the faith, customs, and political beliefs of the more than one billion people who call themselves Muslims